A FRESH PERSPECTIVE ON ’THE WANDERING EARTH II’: PEIRCE’S SEMIOTICS IN FILM ART CREATION - Zhang, XiaoLi (Economics and Statistics Research Journal (ESRJ), 2023)
This paper explores the symbolic system of the Chinese science fiction series "The Wandering Earth II" using Peirce’s semiotic framework. The analysis employs iconic, indexical, and symbolic symbols to investigate the film’s internal logical structure and its external epochal backdrop. By intertwining the primary narrative about the "Mount Hua Plan" leading Earth to escape the solar system’s Helium Flash catastrophe with the struggle between the "Mountain Movers Faction" and the "Digital Life Faction," the film provides a multidimensional construction and elucidation of themes through interactive interpretation with the audience. Peirce’s semiotic system takes an alternative approach, incorporating diverse elements of human nature, social history, and individual cognition from the external world into his research. The paper examines the film’s profound symbolic representation and intermingling of surrealism with realism narrative, creating a grand narrative context grounded in reality yet transcending it. Indexical symbols form the cause-and-effect adjacency with the objects they represent, offering a more direct relationship than analog ones. The most striking indexical sign in the film is the quantum computer 550W, representing the pinnacle of artificial intelligence technology and MOSS. MOSS not only provides humans with hints before imminent disasters but also serves as the index in constructing the storyline’s inherent narrative logic and perfecting the narrative structure. The film also employs symbolic symbols to reflect the era’s context, allegorizing social reality and demonstrating great power and responsibility. Through its application of symbolic representations, the film conveys the grand concept of a "common human destiny" and strengthens its philosophical discourse. The paper provides semiotic references for future film art creation and offers fresh perspectives on the interpretation of the movie